PENERAPAN MODEL DISCOVERY LEARNING DENGAN MENGGUNAKAN MEDIA VIDEO UNTUK MENINGKATKAN AKTIVITAS BELAJAR DAN HASIL BELAJAR SISWA KELAS XI IPA 1 SMAN 1 KOTA BENGKULU - Sitti Utami Medianty; Amrul Bahar; Elvinawati Elvinawati (University of Bengkulu, 2018)
[APPLICATION OF DISCOVERY LEARNING MODEL BY USING VIDEO MEDIA TO INCREASE LEARNING ACTIVITIES AND STUDENT LEARNING RESULT CLASS XI IPA 1 SMAN 1 BENGKULU CITY]. The research has goals to improve the activity and learning outcomes chemistry at XI IPA 1 class in SMA Negeri 1 Bengkulu that consist of 30 students: 23 girls and 7 boys. This study is research of class action on thermochemistry subjects by discovery learning model. This research consist three cycle on four stage: planning, action, absorption, and reflection. The data collected using test and non test that consist of post test and observation sheet of activity teacher and student. The data processed using quantitative simple analysis techniques: average score of observation sheet of activity teacher and student, average score, absorption percentage clasical, andclasssical learning completness percentage. From the reseult, we can conculded that chemistry learning process applying discovery learning model using video can improve activity and outcomes learning chemistry student. It can be see from the average score of students. In the first cycle is 69.33 in which the percentage of classical absorption is 86.67 and classical learning completeness is 66.67. The average score of the second cycle is 71,33 in which the percentage of classical absorption is 89.17 and classical learning completeness is 73.33. The students’ average score of the third cycle is 81.33 in which the percentage of classical absorption is 90.37 and classical learning completeness is 86.67. The teacher’s activities of the learning process in the first cycle get average score 26.5 and it is good category, the second cycle is 27.5 and it is good category, the third cycle is 30 and it is good category too. Meanwhile, the student’s activities in the first cycle get average score 22.5 and it is good category, the second cycle is 25 and it is a good category, the third cycle is 27 and it is good category.